Trait sensitivity to negative feedback in rats is associated with increased expression of serotonin 5-HT2A receptors in the ventral hippocampus - Surowka, Paulina; Noworyta, Karolina; Smaga, Irena; Filip, Malgorzata; Rygula, Rafal (Frontiers in Molecular Neuroscience, 2023)
One of the most important yet still underappreciated mechanisms of depression is distorted cognition, with aberrant sensitivity to negative feedback being one of the best-described examples. As serotonin has been identified as an important modulator of sensitivity to feedback and because the hippocampus has been implicated in the mediation of learning from positive and negative outcomes, the present study aimed to identify differences in the expression of various genes encoding 5-HT receptors in this brain region between the rats displaying trait sensitivity and insensitivity to negative feedback. The results demonstrated that trait sensitivity to negative feedback is associated with increased mRNA expression of the 5-HT2A receptors in the rat ventral hippocampus (vHipp). Further analysis revealed that this increased expression might be modulated epigenetically by miRNAs with a high target score for the Htr2a gene (miR-16-5p and miR-15b-5p). Additionally, although not confirmed at the protein level, trait sensitivity to negative feedback was associated with increased expression of mRNA encoding the 5-HT7 receptor in the dorsal hippocampus (dHipp). We observed no statistically significant intertrait differences in the expression of the Htr1a, Htr2c, and Htr7 genes in the vHipp and no statistically significant intertrait differences in the expression of the Htr1a, Htr2a, and Htr2c genes in the dHipp of the tested animals. These results suggest that resilience to depression manifested by reduced sensitivity to negative feedback may be mediated via these receptors.